1993
DOI: 10.1111/j.1365-2222.1993.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a house dust mite allergen with common antibody binding specificities with multiple components in mite extracts

Abstract: Plaque radio-immuno assay has been used to isolate an IgE-binding clone from a lambda gt11 library of Dermatophagoides pteronyssinus cDNA. The clone HD6 contained DNA encoding a 215 residue protein which contained a predicted 17 amino acid residue leader sequence, no cysteines and a single N-glycosylation site. The 198 residue mature protein would have a predicted MW of 22,177 D. No homologues were found in searches of the data banks. Sera from 14/38 allergic children reacted strongly with the polypeptide prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 22 publications
6
68
0
Order By: Relevance
“…The interpretation of the studies is however difficult because of variation from report to report, the poor dose-response characteristics of blotting and the lability of allergens. Recent studies have also shown that the group 3, 7 and 14 allergens are found with multiple bands which vary from extract to extract [11, 12, 13]. The use of recombinant techniques has provided a method of examining the allergens without relying on their abundance or stability in extracts.…”
Section: House Dust Mite Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation of the studies is however difficult because of variation from report to report, the poor dose-response characteristics of blotting and the lability of allergens. Recent studies have also shown that the group 3, 7 and 14 allergens are found with multiple bands which vary from extract to extract [11, 12, 13]. The use of recombinant techniques has provided a method of examining the allergens without relying on their abundance or stability in extracts.…”
Section: House Dust Mite Extractsmentioning
confidence: 99%
“…The cDNA encoded 215 residues with no cysteines, a single N-glycosylation site and a predicted 17-residue leader peptide [12]. The mature 198-residue polypeptide had a MW of 22,000.…”
Section: Group 7 Allergensmentioning
confidence: 99%
“…Considerable information is available on many of the major mite allergens, particularly those of the genus Dermatopha goides, either through physicochemical studies of the native proteins [7][8][9][10], or the analysis of the cDNA coding for these, and the evaluation of the expression products of this cDNA [11,12], A particularly important allergen of Dermatophagoidespteronyssinus, designated Dcr p 2, has been ex tensively studied [13,14], and has been cloned and ex pressed in Escherichia coli as a fusion protein with glutathione-S-transferase (GST) [15,16]. We have shown that the recombinant material is closely comparable to the native protein in its capacity to bind specific IgE and to elicit im mediate hypersensitivity reactions in the skin o f house-dust mite-allergic patients [17], Two less well characterized mite allergens, Der p 5 [ 18,19] and Der p 7 [20], have also been cloned, and the recombinant fusion proteins shown to bind IgE and produce positive skin tests.…”
Section: Introductionmentioning
confidence: 99%
“…92 Der p 7-reactive IgE serum antibodies are found in only 53% of allergic patients, 93 however, the scale of the response can be as great as for the more major allergens. 94 )-though with expectedly low sequence identities (14% and 12%, respectively).…”
Section: Case Study #3: Der P 7 From Dermatophagoides Pteronyssinusmentioning
confidence: 99%